2022
DOI: 10.1101/2022.03.09.483628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Floating EMG Sensors and Stimulators Wirelessly Powered and Operated by Volume Conduction for Networked Neuroprosthetics

Abstract: Background: Implantable neuroprostheses consisting of a central electronic unit wired to electrodes benefit thousands of patients worldwide. However, they present limitations that restrict their use. Those limitations, which are more adverse in motor neuroprostheses, mostly arise from their bulkiness and the need to perform complex surgical implantation procedures. Alternatively, it has been proposed the development of distributed networks of intramuscular wireless microsensors and microstimulators that commun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…However, it must be noted that the designed communication protocol allows the control of up to 256 devices per low-level control unit, and the possibility to have several low-level units connected to a high-level controller. In fact, we have in vitro demonstrated that more than 10 floating devices can be wirelessly powered and digitally controlled from the external system (50).…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be noted that the designed communication protocol allows the control of up to 256 devices per low-level control unit, and the possibility to have several low-level units connected to a high-level controller. In fact, we have in vitro demonstrated that more than 10 floating devices can be wirelessly powered and digitally controlled from the external system (50).…”
Section: Discussionmentioning
confidence: 99%
“…However, medical devices relying on built-in batteries present drawbacks, necessitating periodic surgeries for replacements, with associated risks and financial burdens [1]- [11]. To address these challenges, various wirelessly powered technologies, including inductively coupled WPT, capacitively coupled short-ranged WPT, and newer options like ultrasonic, mid-field, and far-field coupled WPT, are widely used for implants and wearables, although challenges persist [1]- [2], [13]- [15], [20]- [23], [35]. Inductive power links face issues like suboptimal performance during misalignments, requiring innovative design solutions [1]- [2], [35].…”
Section: Member Ieeementioning
confidence: 99%
“…Inductive power links face issues like suboptimal performance during misalignments, requiring innovative design solutions [1]- [2], [35]. Near-field capacitive coupling encounters obstacles, including heightened sensitivity to Tx-Rx separation and increased power fluctuations [23], [35]. Ultrasonic energy transfer faces challenges due to varying organ densities, soft tissue attenuation, and sensitivity to distance, potentially impacting overall system performance [1], [21], [35].…”
Section: Member Ieeementioning
confidence: 99%
See 1 more Smart Citation